Ethnobotanical Study of Medicinal Plants Among the Paser Telake Tribe in Pinang Jatus Village, East Kalimantan, Indonesia - Rani, Frederika Erwina; Kustiawan, Paula Mariana (Jurnal Biodjati, 2025)
Ethnobotany is an interdisciplinary field that explores the relationship between humans and plants, particularly in the context of traditional medicinal practices. In many rural and indigenous communities, traditional knowledge of medicinal plants remains essential for primary healthcare, especially where access to modern medical services is limited. Pinang Jatus Village, Paser District, East Kalimantan Province, is one such community where ethnobotanical practices continue to play a significant role in daily life. However, the specific plants used, methods of preparation, and ailments treated have not been systematically documented. This study aimed to identify the types of medicinal plants used by the residents of Pinang Jatus Village, the traditional methods of preparation, and the diseases commonly treated with these plants. A quantitative and descriptive research approach was applied, using purposive and snowball sampling techniques to select 30 informants. The study employed a qualitative framework through in-depth interviews, complemented by quantitative analyses using the Use Value (UV), Informant Consensus Factor (ICF), and Fidelity Level (FL) measures. Data were collected through semi-structured interviews. The study identified 24 plant species used for medicinal purposes, with the Asteraceae family being the most dominant. The most commonly utilized plant parts were leaves, followed by roots and seeds. The findings demonstrate that the community possesses rich ethnobotanical knowledge and continues to rely on a diverse range of plant species for traditional healing. These results not only fulfill the study’s objectives but also emphasize the importance of preserving traditional knowledge and highlight the potential for future pharmacological research based on these local practices.